(untitled) (Scientific journal of the Fergana State University, 2025)
This article focuses on the development of oral speech skills, including listening, pronunciation, speaking, and the cultivation of speech culture. It explores approaches to enhancing communicative abilities through interactive activities, role-playing, and multimedia tools in language teaching. The study analyzes methods for strengthening learners’ ability to communicate freely and confidently in their target language. Research findings indicate that teachers’ innovative approaches and personalized techniques play a significant role in improving the effectiveness of oral skill development. Improving oral speech in English classes is a crucial aspect of language acquisition, focusing on developing students’ speaking skills and enhancing their communicative competence. This process involves the use of various teaching methods such as role-plays, debates, and collaborative tasks, which engage students in authentic communication. Effective strategies for improving oral skills also include utilizing multimedia resources and creating an interactive learning environment. The integration of these methods not only boosts students’ confidence in speaking but also enhances their overall language proficiency, making them more adept in real-life communication situations.